HIV-Specific Antibody Immunity Mediated Through NK Cells and Monocytes - Kramski, Marit; S. Parsons, Matthew; Stratov, Ivan; J. Kent, Stephen (Current HIV Research, 2013)
The partial success of the RV144 trial re-energized the field of HIV vaccine research, which had stalled after vaccines based on neutralizing antibody and cytotoxic T cells had failed to induce protection. A large post-vaccine research effort has focused attention on the role of non-neutralizing antibodies in the protection afforded by the RV144 vaccine. These binding antibodies can initiate immune responses such as antibody-dependent cellular cytotoxicity (ADCC) and antibody-dependent cellular phagocytosis (ADCP) and combine elements of the adaptive and innate immune system in the form of antibodies and effector cells (including NK cells, monocytes and granulocytes). A complex interplay exists between the variable portion of the binding antibody and its HIV antigen target on one hand and the constant region of the antibody and the Fcγ-receptor of the effector cell on the other hand. Technical advances have revolutionized the abilities of scientist to detect the targets of non-neutralizing antibodies, including both envelope and non-envelope epitopes, and their role in forcing escape. Our understanding of the antibody characteristics (including IgG subclasses and Fc glycan profile) is providing valuable insights into their optimal structure and function. We expand on critical research on ADCC effector cells, particularly education of NK cells. We introduce the concept of HIV antibodydependent trogocytosis by monocytes as a potentially important aspect of HIV immunity. In summary, this review highlights recent advances in HIV-specific antibody immunity mediated through NK cells and monocytes.
Keywords: vaccines